High lipoprotein(a) cholesterol in patients with familial hypercholesterolemia - Medeiros, A.M. (2020)
Aim: Familial Hypercholesterolemia (FH) patients have an increased cardiovascular risk due to high TC or LDL-C levels. Lp(a) chemical structure is similar to LDL and elevated Lp(a) is considered an independent risk factor for cardiovascular disease (CVD). Recently, it has been described that in patients with high Lp(a), the Lp(a)-C can contribute up to 25% to 50% of all LDL-C. In the present work we aim to determine if elevated Lp(a) concentrations can contribute to clinical phenotype of FH.